Rural residence and mental health among US Veterans: Findings from the Millennium Cohort Study - Claire A. Kolaja; Javier Villalobos; Julia Seay; Hope S. McMaster; Edward J. Boyko; Rudolph P. Rull (PLoS ONE, 2026)
Background Military veterans are at higher risk of mental health conditions compared to civilians. Some residential characteristics may increase the odds of mental health conditions, but other studies have not examined location attributes (i.e., residential rurality, community social vulnerability, and drive time from Veterans Health Administration [VHA] facilities) and VHA utilization concurrently in association with veteran mental health. Methods We analyzed data from 20,423 veterans enrolled in the Millennium Cohort Study, the longest running and largest study of service members and veterans, who completed one pre- and one post-military separation survey (Time 1 and 2, respectively). Time 2 mailing addresses were used to determine location characteristics, including rurality, social vulnerability, and drive time to VHA facilities. VHA enrollment/utilization and mental health outcomes, including probable PTSD, depression, anxiety, and mental quality of life (QOL), were also measured at Time 2. Models adjusting for Time 1 military, demographic and behavioral characteristics were used to examine the association of location characteristics and VHA enrollment/utilization on mental health. Results Rurality was not associated with the four mental health outcomes examined. VHA utilization was associated with elevated odds of probable PTSD, depression, anxiety, and lower mental QOL. While community social vulnerability trended toward associations with PTSD and depression, it was only statistically associated with higher odds of anxiety. Discussion This study was able to examine residential attributes and VHA utilization on post military mental health. In adjusted models, we found that rurality and drive time to VHA facilities were not associated with mental health. The association between VHA enrollment and utilization with worse mental health was consistent and strong in all models examined.